Penerapan Protokol Kesehatan Terhadap Penanganan Tamu Check-In Pada Masa Pandemi Covid-19 di Six Senses Uluwatu Bali - I Wayan Sunarsa; Ni Kadek Anggairah Lesmanawati; Ni Ketut Iswarini (Program Studi Manajemen Divisi Kamar, 2022)
This study aims to determine the application of health protocols to the handling of check-in guests during the covid-19 pandemic at Six Senses Uluwatu Bali. Methods of data collection with documentation, observation and interviews. The data analysis used by the researcher is a qualitative descriptive technique. This study uses the CHSE (cleanliness, health, safety, environment sustainability) implementation guideline which is a benchmark for the standard of reception of check-in guests at Six Senses Uluwatu Bali during the covid-19 pandemic. The results showed that the application of health protocols to the handling of check-in guests carried out by the receptionist during the covid-19 pandemic at Six Senses Uluwatu Bali was basically in accordance with the standard operating procedure. It was said that from 2 activities, namely preparation and reception of check-in guests with 22 criteria, there were 12 criteria that had been applied 100% and 10 criteria had not been applied 100%. From the results of the study, it can be recommended that receptionist officers are expected to be able to carry out the process of cleaning the work area before starting work (2) periodically spraying disinfectant at least 3 times a day, (3) and ensuring check-in equipment is complete and sterile.